A Study on Website Quality Evaluation based on Sitemap - Chandran M; Ramani A.V (International Journal of Computer Sciences and Engineering, 2014)
Website quality evaluation can be made based on creating site map for the WebPages for a single website which works properly. A website is taken for the analysis where we check every link under that website are checker and split it according to status code. By analyzing every status code from all those webpage links, we are ignoring every other link except the page contains status code 200. Then we are developing the sitemap for those links which is working perfectly.